PROSPEK KERJASAMA PERDAGANGAN INDONESIA – INDIA - Irma Rahmawati (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2007)
This Research was conducated to see the progress of Trade relationship between Indonesia and India , to see global picture of benefit to do a free trade agreements (FTA) with India, to see future prospect of Indonesian Main export Comodities to India. India was Indonesian good Trade partner, and it was shown by the increase of total Trade and also Trade balance in each year. Simulation by WITS-Smart Programme show that realization of FTA between Indonesia and India will benefit for both countries. Simulation of India’s tariff cut show there are an increase on welfare in India and export in Indonesia. Most of main export Comodities have good prospect to increase with FTA realization. Prospect Indicators are seen by copper growth from the wortlh, and the value of Trade total effect that is created by the realization of FTA.